2021
DOI: 10.1126/sciadv.abc2578
|View full text |Cite
|
Sign up to set email alerts
|

Prototypical oncogene family Myc defines unappreciated distinct lineage states of small cell lung cancer

Abstract: Comprehensive genomic analyses of small cell lung cancer (SCLC) have revealed frequent mutually exclusive genomic amplification of MYC family members. Hence, it has been long suggested that they are functionally equivalent; however, more recently, their expression has been associated with specific neuroendocrine markers and distinct histopathology. Here, we explored a previously undescribed role of L-Myc and c-Myc as lineage-determining factors contributing to SCLC molecular subtypes and histology. Integrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 61 publications
(92 reference statements)
6
45
0
Order By: Relevance
“…Among them, MYCL overexpression is associated with the classical NE status of SCLC (primarily ASCL1 subtype) ( 19 ), while the amplification or overexpression of c-MYC is required to maintain the NEUROD1 subtype lineage status and can also appear in SCLC-P and SCLC-Y subtypes ( 6 , 21 ). In this study, replacement of c-MYC with MYCL gene in c-MYC SCLC cells induced cell transition to NE lineage state, which is highly similar to ASCL1-SCLC but could not lead to a complete transition to ASCL1-SCLC, suggesting that it could not completely control the trans-differentiation from NE-low or variant state to NE-high or classical state ( 43 ). However, in human SCLC cell lines and PDX models, c-MYC induced the trans-differentiation from ASCL1-SCLC to variant morphology with NEUROD1 expression ( 33 , 40 ), accompanied by LCNEC-like/variant SCLC histological transition.…”
Section: Tumor Heterogeneity and Plasticity Of Sclcsmentioning
confidence: 69%
See 1 more Smart Citation
“…Among them, MYCL overexpression is associated with the classical NE status of SCLC (primarily ASCL1 subtype) ( 19 ), while the amplification or overexpression of c-MYC is required to maintain the NEUROD1 subtype lineage status and can also appear in SCLC-P and SCLC-Y subtypes ( 6 , 21 ). In this study, replacement of c-MYC with MYCL gene in c-MYC SCLC cells induced cell transition to NE lineage state, which is highly similar to ASCL1-SCLC but could not lead to a complete transition to ASCL1-SCLC, suggesting that it could not completely control the trans-differentiation from NE-low or variant state to NE-high or classical state ( 43 ). However, in human SCLC cell lines and PDX models, c-MYC induced the trans-differentiation from ASCL1-SCLC to variant morphology with NEUROD1 expression ( 33 , 40 ), accompanied by LCNEC-like/variant SCLC histological transition.…”
Section: Tumor Heterogeneity and Plasticity Of Sclcsmentioning
confidence: 69%
“…Thus, it has been proposed that one of the mechanisms by which the NE differentiation program is absent in SCLC, may be mediated by c-MYC in a NOTCH signaling pathway-dependent manner, and the activation of NOTCH signaling is promoted by the activation of its target gene REST , which further promotes HES1 transcription, ultimately leading to “non-NE” phenotype SCLC. However, it has also been proposed that this trans-differentiation can be mediated independent of NOTCH signaling or can be directly activated by REST ( 43 ).…”
Section: Tumor Heterogeneity and Plasticity Of Sclcsmentioning
confidence: 99%
“…In this regard, using genetically engineered mouse models, a recent study demonstrated that the SCLC subtypes are not independent but rather different stages of the dynamic evolution of SCLC (11). Expression of the classic oncogene MYC is hypothesized to be involved in this dynamic, with MYC promoting lineage shifts from SCLC-ASCL1 to SCLC-NEUROD1 and from SCLC-NEUROD1 to SCLC-YAP1 (11,12). We hypothesize that the present case may be in the dynamic transition stage of its neuroendocrine fate, possibly under the influence of the anticancer drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have highlighted an essential role of MYC family genes the development of SCLC and in progression towards YAP1-positive states and a mesenchymal phenotype [40][41][42]. YAP1 drives mechanotransduction and remodeling of the cytoskeleton and ECM that occurs during EMT to potentiate cell growth, differentiation and malignant progression [33][34][35][36][37]43].…”
Section: Discussionmentioning
confidence: 99%